Perspective Insights of Exosomes in Neurodegenerative Diseases: A Critical Appraisal - Jan, Arif Tasleem; Malik, Mudasir A.; Rahman, Safikur; Yeo, Hye R.; Lee, Eun J.; Abdullah, Tasduq S.; Choi, Inho (Frontiers in Aging Neuroscience, 2017)
Exosomes are small membranous entities of endocytic origin. Their production by a wide variety of cells in eukaryotes implicates their roles in the execution of essential processes, especially cellular communication. Exosomes are secreted under both physiological and pathophysiological conditions, and their actions on neighbouring and distant cells lead to the modulations of cellular behaviours. They also importantly assist the delivery of disease causing entities, such as, prions, α-syn, and tau, and thus, facilitate spread to non-effected regions and accelerate the progressions of neurodegenerative diseases. The characterization of exosomes, provides information on aberrant processes, and thus, exosome analysis has many clinical applications. Because they are associated with the transport of different cellular entities across the blood-brain barrier, exosomes might be useful for delivering drugs and other therapeutic molecules to brain. Herein, we review roles played by exosomes in different neurodegenerative diseases, and the possibilities of using them as diagnostic biomarkers of disease progression, drug delivery vehicles, and in gene therapy.